Field‐Controlled Hydroxide Dynamics Drive High‐Valence Surface Reconstruction of Ferromagnetic Alloy Nanocones Toward Efficient Oxygen Evolution - Xie, Minghui; Gao, Ling; Niu, Weixing; Shi, Xinyue; Yeh, Min‐Hsin; Yang, Menghao; Huang, Wei‐Hsiang; Miao, Guo‐Xing; Fu, Jing (Advanced functional materials, 2025)
Transition metal catalysts undergo dynamic surface reconstruction during the oxygen evolution reaction (OER), yet kinetic barriers inherently restrict the formation of high‐valent active species. Here, nanocone‐structured CoFeNi catalysts are designed to synergistically couple electric and magnetic field effects, tailoring interfacial microenvironments for efficient surface reconstruction. The nanocone tips generate intense localized electric fields that concentrate OH − ions, while their curvature amplifies magnetic flux density to extend the OH − distribution. In situ Raman and ATR‐FTIR spectroscopic analyses confirm that this near‐field coupling enriches interfacial OH − , accelerating metal hydroxylation and deprotonation by optimizing proton‐coupled electron transfer (PCET) kinetics. This synergy drives rapid reconstruction of the catalyst surface, promoting the formation of high‐valent Co 4+ species and activating the lattice oxygen mechanism essential for efficient OER. Electrochemical performance confirms that this high‐activity reconstruction leads to a 400% increase in current density at 1.57 V versus RHE under half‐cell conditions, along with a stable operation at 500 mA cm −2 (1.93 V) for over 500 h in a water electrolyzer. By correlating OH − dynamics with PCET‐mediated Co 4+ activation, this study demonstrates morphology‐engineered field manipulation as an effective approach to drive catalyst reconstruction.